Compare and Contrast: Mark Robbins' Borrowed Landscape - Pat Morton; Mark Robbins (Oz, 1995)
Project by Mark Robbins Text by Pat Morton Shakkei, or borrowed landscape, is the Japanese art of visually incorporating distant elements of the landscape into a garden design. In a shakkei garden, a tableau contained within the garden integrates a far view of mountains, trees, or the horizon. The landscape outside the garden is "borrowed" to create the illusion of an infinite expanse of space and view.